Tropical Oral Disease: Analysing Barriers, Burden, Nutrition, Economic Impact, and Inequalities - Rajendra Santosh, Arvind Babu; Jones, Thaon (Frontiers in Nutrition, 2021)
Traditionally, a healthy mouth is a good indicator of good general health. Poor oral hygiene reflects the health of the oral cavity and is a risk factor for overall health. Although oral diseases like dental decay and periodontitis are prevalent, awareness of oral diseases is still limited. Oral disorders include a wide range of diseases that may not be confined to the oral anatomical structures but may be manifestations of systemic diseases. Identification of the risk factors of dental and oral diseases, including socio-economic determinants, plays a major role in the type of oral health care, and in the promotion of dental health awareness. This article reviews oral diseases in the Caribbean and aims to raise awareness of this subject while suggesting a research agenda for the region.